1977
DOI: 10.1039/dc9776300157
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies of electron attachment to fluorocarbons and related compounds

Abstract: Radical anions of three perfluorocycloalkanes and several halogenofluoromethanes have been detected and identified by e.s.r. studies following Y irradiation at 77 K of solid solutions containing up to 5 mol % of the parent co:npound in neopentane or tetramethylsilane. The isotropic e.s.r. spectra of c-C3Fa, c-C4FC and c-C5F10 are photobleached by visible light and show the second-order structure characteristic of 6, 8 and 10 equivalent fluorines, respectively, the total 19F coupling being approximately the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 1 publication
4
54
1
Order By: Relevance
“…A wealth of valuable information also come from mass spectrometry studies; however, care should be taken in this case when extrapolating the results to condensed phases because of the ineffi- In this paper, the properties of the fluoroethers anion radicals are investigated by low-temperature UV-Vis matrix spectroscopy using photoelectrons emitted from N,N 0 -dimethyl paraphenylene diamine (TMPD) at 250-320 nm [40] and, because of solubility problems, the model compound HCF 2 OCF 2 CF 2 OCF 2 HÁ(HFC). The experiments were performed at 77 K using the neat HFC compound or HFC solutions in tetramethyl silane (Fig.…”
Section: The Perfluoroether Anion-radicalsmentioning
confidence: 99%
“…A wealth of valuable information also come from mass spectrometry studies; however, care should be taken in this case when extrapolating the results to condensed phases because of the ineffi- In this paper, the properties of the fluoroethers anion radicals are investigated by low-temperature UV-Vis matrix spectroscopy using photoelectrons emitted from N,N 0 -dimethyl paraphenylene diamine (TMPD) at 250-320 nm [40] and, because of solubility problems, the model compound HCF 2 OCF 2 CF 2 OCF 2 HÁ(HFC). The experiments were performed at 77 K using the neat HFC compound or HFC solutions in tetramethyl silane (Fig.…”
Section: The Perfluoroether Anion-radicalsmentioning
confidence: 99%
“…28 In many of these studies, attachment of secondary electrons to molecules was postulated in order to explain the presence of anions. ESR studies on matrix isolated halocarbons following irradiation also revealed that certain products that exist as weakly bound negative ion complexes could arise from incomplete DEA, 32 suggesting that electron attachment to dissociative molecular states also leads to stabilization due to the constrictive cage effect of the crystalline lattice. The cage effect is similar to the resonance stabilization process; however, there is a subtle difference in the mechanisms between the resonance stabilization and the stabilization due to the cage.…”
Section: Introductionmentioning
confidence: 97%
“…in solution, these values being in good agreement with the degree of charge transfer observed for these complexes in argon matrix. 4,[10][11][12] Figure 4 shows the water hydrogens-chlorine atom radial distribution functions ͑RDF͒. In the case of the neutral molecule, the solutesolvent interaction is not enough to give a well-defined solvation shell around the chlorine atom.…”
Section: A Dissociation Energy Curvesmentioning
confidence: 99%
“…9 The radical anions of organic halides can also be generated by ␥ irradiation in lowtemperature matrices of inert solvents and studied by means of EPR spectroscopy. [10][11][12] The most unstable halide radical anions are characterized as being of * type, i.e., the attached electron resides in a antibonding C-X orbital. Nitroaryl-containing radical anions, which are more persistent have the attached electron in a mixed * -* orbital.…”
Section: Introductionmentioning
confidence: 99%